Aceitabilidade e viabilidade do tele-yoga no tratamento em pacientes com câncer: uma revisão sistemática - Ferreira, Marcos Roberto Figueira (2024)
Introduction: According to the World Health Organization (WHO), it is estimated that millions of people are diagnosed with cancer annually. Traditional interventions are essential in the treatment of cancer, but are often associated with significant physical and psychological side effects. Given this scenario, with advances in communication technologies that allow the provision of care at a distance and with complementary and integrative therapies gaining prominence, Tele-Yoga emerges as an approach that aims not only at the treatment of health conditions, but also at the holistic and psychological well-being of patients. Furthermore, understanding how these elements can be integrated effectively is essential to improve cancer management, and there is a need to systematically review the existing literature of studies involving the online delivery of yoga for patients undergoing cancer treatment, which has not been done to date. Objectives: To summarize, based on pre-existing evidence, the acceptability and feasibility of tele-yoga for individuals diagnosed with cancer. Methods: This is a systematic review that was conducted and planned in accordance with PRISMA and the protocol registered in PROSPERO. Full articles found in the following databases were used: Biblioteca Virtual de Saúde (BVS), Excerpta Médica Database (Embase), Cochrane Central Register for Controlled Trials (CENTRAL), Medical Literature Analysis and Retrieval System Online (MEDLINE), Scopus and Web of Science. Results: Nine original studies were included in this systematic review. The findings indicate that tele-yoga has been widely acceptable and feasible in several populations of cancer patients, with benefits observed in both physical and mental health. It is worth noting that although there are initial and ongoing costs associated with the use of technology, especially for low-income patients and for the institutions that offer the service, tele-yoga may, overall, be a more economical and sustainable option. Conclusion: The implementation of tele-yoga as a complementary intervention for cancer patients has shown promising results, both in terms of acceptability and feasibility. However, challenges related to technology, such as unequal access to devices and the internet, as well as familiarity with digital platforms, may limit adherence and cause sample losses.